2014
DOI: 10.1021/bc500474p
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Carbonaceous Nanodots for Noninvasive Glioma Imaging after Angiopep-2 Decoration

Abstract: Fluorescent carbonaceous nanodots (CDs) have attracted much attention due to their unique properties. However, their application in noninvasive imaging of diseased tissues was restricted by the short excitation/emission wavelengths and the low diseased tissue accumulation efficiency. In this study, CDs were prepared from glucose and glutamic acid with a particle size of 4 nm. Obvious emission could be observed at 600 to 700 nm when CDs were excited at around 500 nm. This property enabled CDs with capacity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…The particle size of the CDs was 4.9 nm, and the size increased to 8.3 nm after PEGylation (Figure 1), which was consistent with our previous studies [24,25] . According to TEM, the CDs were all spherical and were well dispersed with an average size of 3-4 nm ( Figure 1C); in comparison, the TEM size of PEG-CDs was similar to that of the CDs, which was consistent with results from our previous study [26] .…”
Section: Characterization Of Cds and Peg-cdssupporting
confidence: 91%
“…The particle size of the CDs was 4.9 nm, and the size increased to 8.3 nm after PEGylation (Figure 1), which was consistent with our previous studies [24,25] . According to TEM, the CDs were all spherical and were well dispersed with an average size of 3-4 nm ( Figure 1C); in comparison, the TEM size of PEG-CDs was similar to that of the CDs, which was consistent with results from our previous study [26] .…”
Section: Characterization Of Cds and Peg-cdssupporting
confidence: 91%
“…In vivo results demonstrated that CNP could target the heart, in which the fluorescent intensity was much higher than that in other organs, even liver, and spleen. Furthermore, Green emissive CDs prepared from glucose and glutamic acid by the pyrolysis route [104]. Angiopep-2 is one such ligand whose receptor is low-density lipoprotein receptor-related protein-1 (LRP1) that is overexpressed in glioma cells [105].…”
Section: Fluorescent Cds Conjugated With Targeting Unitmentioning
confidence: 99%
“…Another Angiopep-2 targeting agent, with Angiopep-2 anchored to carbonaceous nanoparticles, allows for NIR imaging and preferential targeting of orthotopic C6 glioma models, with a TNR of 1.73. 69 Angiopep-2 has been linked to gadolinium for use with preoperative MRI and surgical planning, 67 and to chemotherapeutic and phototherapeutic agents for brain tumor treatment. 70-73 A combination of Angiopep-2 targeting with activating cell penetrating peptide (ACP) and the chemotherapeutic agent docetaxel generated a more potent chemotherapeutic than without the ACP fragment in a mouse orthotopic glioma model.…”
Section: Targeted Fluorescent Molecular Imaging Agentsmentioning
confidence: 99%